Dental Phobia in Medical Students of Lahore Medical and Dental College, Lahore, Pakistan - Noor Fatima, Muhammad Ahsan Masood, Eisha Taimoor, Nimrah Bilal, Khurram Nadeem, Faiza Ajmal, Roha Zubair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental phobia the fear to dental procedures, dental instruments or dentist is the common fear among people of all ages that cause delay of dental treatments. By finding out the response of students towards dental treatment will help in the apprehension and overcoming the dental phobia. The purpose of this study conducted in LMDC among the medical graduates was to know the prevalence of dental phobia in them. Method: A cross sectional study was conducted to access the dental phobia among the BDS, MBBS, DPT and Pharm D students of Lahore Medical and dental college using the MDAS . Descriptive statistics including means, standard deviations, and percentages were calculated. Group comparisons were analyzed using t-tests and analysis of variance. Multiple group comparisons were conducted using Tukey’s post-hoc test. P < 0.05 was considered as the significance level. Results: Three hundred students took part in this study. Equal number of response was recorded by BDS, MBBS, DPT and Pharm D students. There was significant difference seen in dental phobia among gender. Females had higher level of dental phobia than males. Past negative dental experiences have valid impact on people and lead to increased prevalence towards dental phobia. Dental students exhibited the least amount of dental phobia. Conclusion: BDS students had lowest level of dental phobia. By increasing the dental health education and awareness about oral health the dental phobia can be reduced among people Keywords: Dental student, Dental phobia, Anxiety Scale.